Structure and dynamics of mica-confined films of [C(10)C(1)Pyrr][NTf2] ionic liquid - De Freitas, AA; Shimizu, K; Smith, AM; Perkin, S; Lopes, JN (American Institute of Physics, 2018)
The structure of the ionic liquid 1-decyl-1-methylpyrrolidinium bis[(trifluoromethane)sulfonyl]imide, [C10C1Pyrr][NTf2], has been probed using Molecular Dynamics (MD) simulations. The simulations endeavour to model the behaviour of the ionic liquid in bulk isotropic conditions and also at interfaces and in confinement. The MD results have been confronted and validated with scattering and surface force experiments reported in the literature. The calculated structure factors, distribution functions, and density profiles were able to provide molecular and mechanistic insights into the properties of these long chain ionic liquids under different conditions, in particular those that lead to the formation of multi-layered ionic liquid films in confinement. Other properties inaccessible to experiment such as in-plane structures and relaxation rates within the films have also been analysed. Overall the work contributes structural and dynamic information relevant to many applications of ionic liquids with long alkyl chains, ranging from nanoparticle synthesis to lubrication.